Epidemiology of Staphylococcus Aureus Clinical Isolates Causing Skin and Soft Tissue Infections Among Patients in the Community Settings At Primary Healthcare Centres in Sidoarjo Region-East Java, Indonesia - Sugiharto . (Journal of Global Pharma Technology, 2019)
Objectives To determine percentage of case finding of Staphylococcus aureus, methicillin resistant Staphylococcus aureus (MRSA) and panton–valentine leukocidin (PVL)-positive Staphylococcus aureus (S. aureus) isolated from skin and soft tissue infections in the community settings at Primary Healthcare Centres in Sidoarjo region, Indonesia and the relationship of risk factors of Staphylococcal skin and soft tissue infections. Methods S. aureus isolates from clinical cultures of patients in 2 Primary Healthcare Centres were included. Wound cultures were performed to identify the MRSA phenotypically using VITEK® 2 system. The mecA gene and genes encoding PVL were detected using Polymerase Chain Reaction (PCR). Clinical data including gender, age, hospitalization history in primary health care center and hospital, comorbidity (diabetes mellitus) history and antibiotic history, were collected from questionnaires and medical record. Statistical analysis was done by Chi-square-Fisher’s exact test. Results In total, 45 patients involved in this study. The 20 patients consisted Staphylococcal strain, and 25 patients did not. Of the 20 Staphylococcal strains, 3 samples were Staphylococcus coagulase negative, 1 sample was Staphylococcus gallinarum and another sample was Staphylococcus haemolyticus. There were 15 patients (33.3%) were infected by S. aureus. Of these, 13 isolates were MRSA-positive (28,9%) and 1 isolate was PVL-positive (2,2%). Analysis showed no relationship between the risk factors and finding of S. aureus, neither MRSA and PVL in all patients (p > 0.05).Conclusions S. aureus is common in the community. The MRSA is clinical importance in Indonesia, not only in hospitals, but also in the community settings. High case of MRSA was found in this study. However, the case of PVL-positive S. aureus was low. It is very important to promote case finding by detecting MRSA in the community settings. A national surveillance system should be set-up for further monitoring this.Keywords Methicillin-resistant S. aureus, Panton–valentine leukocidin, Staphylococcus aureus, community setting, Prevalence.